Intracranial Solitary Fibrous Tumor in a 25-Year-Old Woman - Prasetyo, Patricia Diana; Marisca, Stephanie; Wahjoepramono, Eka J. (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Introduction: Intracranial solitary fibrous tumors (ISFTs) are extremely rare spindle cell tumors originating from dendritic mesenchymal cells expressing CD34 antigens that are usually benign, although malignant transformation had been reported. The knowledge of natural course and prognostic factors of ISFTs is still limited and the tumor is easily misdiagnosed.Case Presentation: An intra-cranial extra-axial tumor tissue resection from a 25-year-old woman was evaluated in the Surgical Pathology Laboratory. Histologic findings (cellular spindle cell tumor with ”˜patternless’ pattern, staghorn blood vessels and <5 mitoses per 10 hpf) and immunophenotype (positive for CD34, weakly and focally positive for STAT6) suggested a diagnosis of intracranial solitary fibrous tumor WHO Grade II.Discussion: ISFTs have very low incidence in the CNS and are difficult to distinguish radiologically from meningiomas, thus post operative pathological examination and immunohistochemistry markers evaluations are the mainstay for diagnosis. ISFT is associated with NAB2-STAT6 gene fusion and may exhibits a wide spectrum of histological features. STAT6 immunohistochemistry is considered as one of the most sensitive diagnostic methods, while the evaluation of CD34 expression can be used as alternative diagnostic method despite having lower sensitivity.